E-business and export behavior : evidence from Indian firms (2004)
Identifies and analyzes the factors that have influenced the export performance of firms in the post-liberalization era of the Indian economy. Concludes that the performance of firms in international markets has been better for those that have adopted more advanced e-business tools.
Keywords: EXPORTS